Determinantes da participação dos beneficiários no programa do Rendimento Mínimo Garantido no mercado de trabalho - Fortuna, Mário (2011)
We present micro econometric evidence on the determinants of the probability that beneficiaries of the Minimum Guaranteed Income (MGI) participate in market production or in home production. We use a micro data set which covers all the beneficiaries of the MGI, up to 2001, for the Portuguese Region with the highest incidence of this program, namely, the Azores. We find striking diferences between women’s and men’s behaviour with respect to labour market participation decisions, with women heavily specialized in home production and men in market production. The probability of participating decreases with income support. Moreover, there are several aspects of household demographics that matter to female participation decisions. Therefore, policies designed to promote female labour supply should not be of the type one size fits all and must improve the terms of trade between home production and market production for women.